A Multidimensional, Multisensory and Comprehensive Rehabilitation Intervention to Improve Spatial Functioning in the Visually Impaired Child: A Community Case Study - Morelli, Federica; Aprile, Giorgia; Cappagli, Giulia; Luparia, Antonella; Decortes, Francesco; Gori, Monica; Signorini, Sabrina (Frontiers in Neuroscience, 2020)
Congenital visual impairment may have a negative impact on spatial abilities and result in severe delays in perceptual, social, motor, and cognitive skills across life span. Despite several evidences have highlighted the need for an early introduction of re-habilitation interventions, such interventions are rarely adapted to children’s visual capabilities and very few studies have been conducted to assess their long-term efficacy. In this work, we present a case study of a visually impaired child enrolled in a newly developed re-habilitation intervention aimed at improving the overall development through the diversification of re-habilitation activities based on visual potential and developmental profile, with a focus on spatial functioning. We argue that intervention for visually impaired children should be a) adapted to their visual capabilities in order to increase re-habilitation outcomes, b) multi-interdisciplinary and multidimensional, in order to improve adaptive abilities across development, c) multisensory, to promote the integration of different perceptual information coming from the environment.